Irreconcilable times. (20th May 2022) - Mookherjee, Nayanika
Abstract: In Denktagebuch ( Thought diary, 1950‐73), Hannah Arendt wrote that acts which cannot be forgiven are beyond punishment and hence cannot be reconciled to. In this essay, I draw from Arendt to further theorize and extend the concept of irreconciliation. I draw together ethnographic material, historical material, documents, media reports, and reviews during this era of irreconcilability which includes Black Lives Matter; the memorialization debates on the removal of statues of enslavers; the history of slavery in the United Kingdom; and the 'harmony ideology' experienced by BAME (Black, Asian, and minority ethnic) academics within UK organizations linked to long‐term discrimination. I argue for the concept of irreconciliation as a bulwark against impunity, against a 'window‐dressed', symbolic performance of redress, and to be able to echo Arendt's words that 'this' – any original cause of injustice – 'ought never to have happened'. Abstrait: Temps irréconciliables Résumé Dans son Denktagebuch ( Journal de pensée, 1950‐73), Hannah Arendt a écrit que les actes qui ne pouvaient pas être pardonnés étaient au‐delà du châtiment, donc hors de portée de la réconciliation. L'autrice de cet article y puise inspiration pour théoriser davantage et élargir le concept d'irréconciliation. Cet article combine matériaux ethnographiques et historiques, documents, articles de presse et rapports durant une époque d'irréconciabilité qui a vu Black Lives Matter, les débats mémoriels sur l'enlèvement des statues d'esclavagistes, l'histoire de l'esclavage au Royaume‐Uni et l'idéologie « de l'harmonie » à laquelle font face des universitaires noirs, asiatiques et membres de minorités ethniques (« BAME ») au sein d'organisations liées à des discriminations de longue durée au Royaume‐Uni. Elle avance des arguments pour le concept d'irréconciliation comme rempart contre l'impunité, contre un redressement des torts symbolique, « d'affichage », faisant par là écho aux mots d'Arendt selon lesquels « cela » (toute cause originelle d'injustice) « n'aurait jamais dû arriver ».